Students’ Perspectives on Mental Health: Using World Cafés to Engage in Dialogue about Health Promotion and Support Services - de Moissac, Danielle; Waddell. M, Candice M.; Smith, Nadine; Rocque, Rhéa (Collected Essays on Learning and Teaching, 2020)
With the increased incidence of poor mental health in young adults, health promotion strategies are needed on campuses. World Cafés were held to facilitate discussion around three main topics: thoughts about findings emerging from a recent health survey, resources currently available on campus, and strategies or resources needed to improve student well-being. Participants readily provided insight into mental health concerns among students, and their recommendations focused primarily on creating a culture of well-being in the university with more professional support services and greater health promotion. Overall, the World Café approach provided an effective method to engage students and discuss possible strategies to promote better mental health on campus. Étant donné l’augmentation des problèmes de santé mentale chez les jeunes adultes, il faut adopter des stratégies de promotion de la santé à l’université. Des conversations de type Café du monde – World Café – ont eu lieu autour de trois sujets : 1) des réflexions autour des résultats provenant d’un sondage récent pourtant sur la santé; 2) les ressources qui sont actuellement offertes à l’université; 3) les stratégies et les ressources nécessaires à l’amélioration du bien-être des étudiants. Les participants n’ont pas hésité à témoigner des enjeux de santé mentale dans la communauté étudiante. Leurs recommandations ont convergé principalement vers la création d’une culture du bien-être à l’université, ce qui suppose un accroissement des services d’aide professionnelle et de la promotion de la santé. Dans l’ensemble, la méthode de type Café du monde a permis de faire participer les étudiants et de discuter des stratégies potentielles pour la promotion de la santé mentale à l’université.

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final - Léger (Santé Canada, 2020)